SOCIO-CULTURAL CONTEXT OF STUDENT’S PERCEPTION OF THE UNIVERSITY CORPORATE CULTURE VALUES - Sliusarevskyi, Nazar M. (Educological discourse, 2016)
The article deploys the results of the study “Peculiarities of perception of the principles of corporate culture by faculty and students of Borys Grinchenko Kyiv University (BGKU)” to show how important is to use vital values by Sh. Schwartz in pedagogic communication in student community. This can facilitate or hinder the successful assimilation of corporate culture values by students. The study found that the values of benevolence, universalism and stimulation had positive effect on corporate culture assimilation of students of BGKU, while the value of hedonism had negative effect.